EVALUATION OF THE CIPP MODEL IN THE PEDESTRIAN LANE PROGRAM ON DR MANSYUR STREET, MEDAN CITY - Ridoi Sihura; Zoraya Alfathin Rangkuti (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
The pedestrian path program is one of the Medan City Government's efforts, through the Highways Division of the SDABMBK Office, to provide safe, comfortable, and user- friendly road infrastructure for all users, including people with disabilities. This study aims to launch the pedestrian path program on street Dr. Mansyur, Medan, This study employed a qualitative descriptive approach, with data collection techniques including in-depth interviews, field observations, and documentation. This study also using the CIPP (Context, Input, Process, Product) evaluation model. The results indicate that, in terms of context indicators, the program has achieved its intended target but has not yet optimally addressed pedestrian needs. In terms of input indicators, human and institutional resources are adequate, but budget allocation is suboptimal. In terms of process indicators, implementation has been ineffective due to a lack of coordination between programs and a lack of ongoing maintenance. In terms of product indicators, the sidewalks constructed do not meet minimum pedestrian infrastructure service standards, in terms of function, safety, and aesthetics. Based on these findings, it is recommended that the Medan City Government establish comprehensive sidewalk rehabilitation priorities, establish a cross-regional coordination team, and implement regular evaluations of pedestrian infrastructure conditions